Influence of YES1 Kinase and Tyrosine Phosphorylation on the Activity of OCT1 - Uddin, Muhammad Erfan; Garrison, Dominique A.; Kim, Kyeongmin; Jin, Yan; Eisenmann, Eric D.; Huang, Kevin M.; Gibson, Alice A.; Hu, Zeping; Sparreboom, Alex; Hu, Shuiying (Frontiers in Pharmacology, 2021)
Organic cation transporter 1 (OCT1) is a transporter that regulates the hepatic uptake and subsequent elimination of diverse cationic compounds. Although OCT1 has been implicated in drug-drug interactions and contributes to pharmacokinetic variability of many prescription drugs, details of the molecular mechanisms that regulate the activity of OCT1 remain incompletely understood. Based on an unbiased phospho-proteomics screen, we identified OCT1 as a tyrosine-phosphorylated transporter, and functional validation studies using genetic and pharmacological approaches revealed that OCT1 is highly sensitive to small molecules that target the protein kinase YES1, such as dasatinib. In addition, we found that dasatinib can inhibit hepatic OCT1 function in mice as evidenced from its ability to modulate levels of isobutyryl L-carnitine, an OCT1-specific biomarker identified from a targeted metabolomics analysis. These findings provide novel insight into the post-translational regulation of OCT1 and suggest that caution is warranted with polypharmacy regimes involving the combined use of OCT1 substrates and kinase inhibitors that target YES1.